Granulocyte Colony-Stimulating Factor Receptor Mutations in Myeloid Malignancy - Liongue, Clifford; Ward, Alister Curtis (Frontiers in Oncology, 2014)
Granulocyte colony-stimulating factor (G-CSF) is a cytokine able to stimulate both myelopoiesis and hematopoietic stem cell mobilization, which has seen it used extensively in the clinic to aid hematopoietic recovery. It acts specifically via the homodimeric, granulocyte colony-stimulating factor receptor (G-CSFR), which is principally expressed on the surface of myeloid and hematopoietic progenitor cells. A number of pathogenic mutations have now been identified in CSF3R, the gene encoding G-CSFR. These fall into distinct classes, each of which is associated with a particular spectrum of myeloid disorders, including malignancy. This review details the various CSF3R mutations, their mechanisms of action and contribution to disease, as well as discussing the clinical implications of such mutations.